Magnetic characteristics of nanocrystalline GaMnN films deposited by reactive sputtering - Leite, D. M G [UNESP]; Pereira, A. L J [UNESP]; Iwamoto, W. A.; Pagliuso, P. G.; Lisboa Filho, Paulo Noronha [UNESP]; Silva, José Humberto Dias da [UNESP] (Elsevier, 2013)
The magnetic characteristics of Ga1-xMnxN nanocrystalline films (x = 0.08 and x = 0.18), grown by reactive sputtering onto amorphous silica substrates (a-SiO2), are shown. Further than the dominant paramagnetic-like behaviour, both field- and temperature-dependent magnetization curves presented some particular features indicating the presence of secondary magnetic phases. A simple and qualitative analysis based on the Brillouin function assisted the interpretation of these secondary magnetic contributions, which were tentatively attributed to antiferromagnetic and ferromagnetic phases. © 2012 Elsevier Masson SAS. All rights reserved.
Keywords: Diluted magnetic semiconductor; GaMnN; Magnetic properties; Nanocrystalline material; Sputtering; Amorphous silica; Antiferromagnetics; Brillouin functions; Diluted magnetic semiconductors; Ferromagnetic phasis; Magnetic characteristic; Magnetic contribution; Magnetization curves; Nanocrystalline films; Nanocrystallines; Qualitative analysis; Secondary magnetic phasis; Temperature dependent; Antiferromagnetism; Gallium alloys; Magnetic semiconductors; Manganese; Nanocrystalline materials; Paramagnetism; Semiconducting gallium; Silica; Amorphous films